WALINGHEALTH INTEGRATION TO SUPPORT THE ACHIEVEMENT OF THE SDGS IN LEUWEUNGKOLOT BOGOR VILLAGE - Anwar, Syaiful; Muhlis, Muhlis; Hamzah, Zeze Zakaria; Rahmania, Nazwa; Hardianti, Dwi Tiara (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Waste management and environmental health remain major challenges in Leuweungkolot Village, potentially hindering the achievement of sustainable development. The situational analysis revealed that most residents lack awareness and skills in waste segregation and environmental health practices. This condition has led to household waste accumulation, low hygienic behavior, and limited institutional capacity at the village level to address environmental issues. The proposed solution through the Walinghealth program includes education, community mentoring, and the establishment of local groups focusing on waste management, recycling, and participatory-based health improvement. The program is integrated with institutional strengthening at the village level to ensure long-term sustainability. The implementation results show increased community awareness, the formation of local environmental groups, and the availability of a simple waste management system at the village level. Thus, the integration of the Walinghealth program provides tangible impacts for the community and supports the achievement of sustainable development goals at the village scale.